Manipulations with early mouse embryos for generation of genetically modified animals - A. N. Korablev; I. A. Serova; B. V. Skryabin (Вавиловский журнал генетики и селекции)
Recently, genome-editing technologies have  become more efficient and accessible. The discovery of nucleases for directional genome editing (CRISPR/Cas9, TALEN, ZFNs) significantly accelerated and simplified the production of mice with targeted gene editing in the genome. Until last time, the CRISPR/Cas9 system noticeably simplified the preparation of knockout or transgenic mice. CRISPR/Cas9 technology was successfully applied for gene knockout and knock-in, generation of large deletions or directed insertions in targeted genome regions in embryonic stem cells (ESCs).When injected into blastocysts, such  modified ESCs are able to generate chimeras producing gametes with an identical genotype with ESC. Thus, it can identify animals with modified genomes. More recently, CRISPR/Cas9 technology was successfully applied to mouse zygotes and the birth of genetic modified mice was observed, i. e., the time required for generating genome-modified animals decreased significantly. The CRISPR/Cas9 system allows making gene knockout, large deletions or directed insertions into the target region of the genome by cytoplasm or pronuclear microinjection into zygotes. In addition, this is faster and simpler than similar work with mouse ESCs. Meanwhile, methods of manipulation with early embryos and their transplantation to surrogate mothers may be somewhat tricky. Therefore, it is important to use modern technologies for directional genome editing and perfect mastery in the embryological technics. In this article, we describe the protocols of microinjection into the pronucleus or cytoplasm of zygotes and injection of embryonic stem cells into the blastocyst cavity. We also describe embryological methods, such as superovulation, preparation of early stage  embryos,  surgical operation, production of foster mice. In addition, we describe the assembly and necessary components for the isoflurane anesthetic apparatus and isoflurane anesthesia.